Environment statistics : pocketbook: data 1980-1999. (Theme 8: Environment and energy. Collection, Key indicators, 2001)
Summary: This booklet summarises the most important figures collected or calculated by Eurostat in the field of environment statistics. It explains the figures by giving backround information on related environmental problems and it indicates the most important political objectives. This booklet gives information on the pressure of the economy on the environment, such as the emissions of various pollutants, the consumption of natural resources, and the pollution waste. A closely related topic, also treated in this edition is the integration of environmental concerns into the various policy field, such as agriculture, transport or energy.